Nutrition Trends in Kidney Transplant Recipients: the Importance of Dietary Monitoring and Need for Evidence-Based Recommendations - Nolte Fong, Joy V.; Moore, Linda W. (Frontiers in Medicine, 2018)
Many physiological properties of the renal system influence nutrient metabolism, elimination, and homeostasis. Kidney failure poses significant challenges to maintaining adequate nutrition, most of which transplantation ameliorates. Comprehensive recommendations for managing nutritional derangements for patients with chronic kidney disease and end stage renal disease exist; however, there are only sparse guidelines for post-transplant malnutrition and adverse outcomes. Not only are guidelines limited, but little is known about dietary trends of post-kidney transplant recipients. This review describes guidelines for prevalent metabolic and nutritional complications post-kidney transplantation and also evaluates changes in caloric intake and diet composition after transplantation. This topic is important because nutrition influences allograft function and a number of cardiovascular risk factors including blood pressure, dyslipidemia, weight, and diabetes. In addition, many dietary recommendations and modifiable lifestyle changes should be tailored for specific complications of transplant patients, namely immunosuppression side effects, dietary restrictions, and electrolyte imbalances.